2015
DOI: 10.1039/c4cc06766e
|View full text |Cite
|
Sign up to set email alerts
|

A photoCORM nanocarrier for CO release using NIR light

Abstract: Amphiphilic polymer conjugates with upconverting nanoparticles serve as water-soluble nanocarriers for NIR-photochemical delivery of CO from hydrophobic photoCORMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
117
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 42 publications
0
117
0
Order By: Relevance
“…However, there have been few reports on the effects of CO released into cells and tissues by light irradiation of the photoactive CORMs. [36][37][38] To adapt the reactivities of photoactive CORMs to cellular environments,i ti se ssential to design scaffolds with improved biocompatibility such as proteins because several proteins have great potential to deliver CORMs. [39][40][41][42][43] In this work, we developed ap hotoactive CO-releasing protein based on ferritin (Fr), an iron storage protein.…”
mentioning
confidence: 99%
“…However, there have been few reports on the effects of CO released into cells and tissues by light irradiation of the photoactive CORMs. [36][37][38] To adapt the reactivities of photoactive CORMs to cellular environments,i ti se ssential to design scaffolds with improved biocompatibility such as proteins because several proteins have great potential to deliver CORMs. [39][40][41][42][43] In this work, we developed ap hotoactive CO-releasing protein based on ferritin (Fr), an iron storage protein.…”
mentioning
confidence: 99%
“…Ford and co-workers showedt hat the NIR irradiation of UCNPs loaded with either the Roussin black salt anion or the photoactivated CO-releasing moiety (photoCORM) trans-[Mn(2,2'-bipyridine)(PPh 3 ) 2 (CO) 2 ] results in the release of NO and CO, respectively. [13,14] Similarly, we have demonstrated that related upconversion nanosystems promoted the release of pyridine fromaR u-polypyridyl complex [16] and the generation of aP t II speciesf rom aP t IV prodrug candidate. [17] Alternatively,H ee tal.…”
Section: Introductionmentioning
confidence: 91%
“…58 Ford and co-workers utilized Tm and Yb-doped NaGdF 4 upconversion nanoparticle (UCNP) as a template for the construction of CORMs. 58 When the UCNP is irradiated with NIR light, the molecule emits visible range photons which have the potential to trigger CO release.…”
Section: Synthetic Polymer Materialsmentioning
confidence: 99%
“…58 Ford and co-workers utilized Tm and Yb-doped NaGdF 4 upconversion nanoparticle (UCNP) as a template for the construction of CORMs. 58 When the UCNP is irradiated with NIR light, the molecule emits visible range photons which have the potential to trigger CO release. To achieve NIR-induced CO release, the UCNP and a [Mn(bpy)(CO) 2 (PPh 3 ) 2 ] + complex were simultaneously encapsulated in an amphiphilic phospholipidfunctionalized PEG micelle (Fig.…”
Section: Synthetic Polymer Materialsmentioning
confidence: 99%